The Essence and the Peculiarity of Conceptions of Social and Pedagogical Support of Childhood in Russia, the Ukraine and the Belarus Republic - Rizhova, Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article says about the main theories and concepts of childhood social and pedagogical support in Russia, the Ukraine and the Belarus Republic. There singled out the main trends of the social-pedagogical and psychological support to the children which suffer from a difficult living conditions. Also the author determines the goals of international cooperation of CIS countries in the sphere of staff training for state institutions of child support.